2015
DOI: 10.1002/zoo.21234
|View full text |Cite
|
Sign up to set email alerts
|

Perception of available space during chimpanzee introductions: Number of accessible areas is more important than enclosure size

Abstract: Restricting animals to different areas of their enclosure, for both brief and extended durations, is a key element of animal management practices. With such restrictions, available space decreases and the choices the animals can make are more limited, particularly in relation to social dynamics. When unfamiliar individuals are introduced to each other, group dynamics can be unpredictable and understanding space usage is important to facilitate successful introductions. We studied the behavioral, welfare-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…In this study we measured the evenness of enclosure use, which represents the functional space of the enclosure rather than available space. We found that small variations in enclosure sizes do not associate with significant shifts in behavioural welfare of Asiatic lions, which is in line with previous studies that place more importance on enclosure design (Tan et al, 2013), complexity and species-appropriateness than enclosure area (Rose & Robert, 2013;Herrelko, Buchanan-Smith & Vick, 2015;Neal Webb, Hau & Schapiro, 2018). The correlation between enclosure size and space usage bias was weak but positive, which means that increasing enclosure sizes were associated with higher zone-usage bias.…”
Section: Discussionsupporting
confidence: 90%
“…In this study we measured the evenness of enclosure use, which represents the functional space of the enclosure rather than available space. We found that small variations in enclosure sizes do not associate with significant shifts in behavioural welfare of Asiatic lions, which is in line with previous studies that place more importance on enclosure design (Tan et al, 2013), complexity and species-appropriateness than enclosure area (Rose & Robert, 2013;Herrelko, Buchanan-Smith & Vick, 2015;Neal Webb, Hau & Schapiro, 2018). The correlation between enclosure size and space usage bias was weak but positive, which means that increasing enclosure sizes were associated with higher zone-usage bias.…”
Section: Discussionsupporting
confidence: 90%
“…Malcolm et al, 1997;Wagaman et al, 1998;Thame et al, 2000), and so a 'social hypothesis' may fit for (some) non-human great apes as well. Baker and Easley (1996) found no relationship between R/R and social disturbance in their Chimpanzee study; similarly, Herrelko et al, (2015) found no change in R/R during the merging and introduction of two chimpanzee groups. In contrast, Miller & Tobey (2012) investigated R/R in 14 Bonobos housed at two zoos undergoing management changes in their group social structure.…”
Section: Social Factorsmentioning
confidence: 92%
“…In contrast, R/R has been documented to occur in at least some individual animals, across nearly all zoo-housed species of great apes, including Chimpanzees Pan troglodytes (e.g. Baker & Easley, 1996;Baker, 1997;Herrelko et al, 2015), Orangutans Pongo sp (e.g. Cassella et al, 2012), Bonobos Pan paniscus (Miller & Tobey, 2012), and Western lowland gorillas Gorilla gorilla gorilla (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Individual NZP orangutans also showed significant preferences for particular rooms within buildings and locations within rooms. A preference for an off-exhibit room was detected for some individuals, confirming the importance of offering choice (Herrelko et al, 2015) to orangutans to use off-exhibit space in the late afternoon as they settle into their night nests.…”
Section: Discussionmentioning
confidence: 66%